CARBON FOOTPRINT IDENTIFICATION OF READY MIX CONCRETE IN BUILDING PROJECT - Daniswara Putra Satya; Ryan Faza (International Journal on Livable Space, 2021)
Construction projects have a major impact on environmental damage, which causes the phenomenon of the greenhouse gas effect and an increase in carbon dioxide. One of the main causes is development. One of the largest producers of carbon dioxide is the Portland cement industry and contributes approximately 7% of the world's carbon footprint. This study aims to identify the amount of carbon footprint generated in the process of using ready mix concrete starting from the contract process, the delivery process, and the use of a concrete pump and determine the influence factors in the process on carbon emissions. This research was also conducted at Luxury Apartment Project located in Dharmawangsa, Kebayoran Baru, South Jakarta. This research method uses a quantitative descriptive research method. The results of the carbon emission calculation assistance are, during the mobilization process at the time of the contract it was 37.6302 kg.CO2, the shipping process was 2.725.7823 kg.CO2, and the use of a concrete pump was 4.284.61186 kg.CO2. The results showed that the amount of carbon emissions has a significant effect on the variable length of travel time, fuel usage, and engine capacity. Keywords: Carbon Emissions, Construction project, Ready Mix Concrete.